Novel exact and solitary solutions of conformable Klein–Gordon equation via Sardar-subequation method - Hussain, Rashida; Imtiaz, Ansa; Rasool, Tayyiaba; Rezazadeh, Hadi; İnç, Mustafa (Shanghai Jiaotong University, 2022)
In this study, the conformable Klein–Gordon equation (KGE) has been investigated. The conformable nonlinear mathematical model has been converted into ordinary differential equation by means of wave transformation and properties of conformable derivative. Sardar-subequation method has been utilized to obtain solutions in terms of trignometric and hyperbolic functions. Consequently, some important solitary wave solutions and novel exact solutions of the considered model has been extracted. © 2022
Keywords: Klein–Gordon equation; Sardar-subequation method; Solitary wave solutions